Flavonoids from Tartary Buckwheat Seeds - Wang, Baixing; Hu, Haobin (Asian Journal of Chemistry, 2012)
Nine flavonoids were isolated from the seeds of tartary buckwheat. Their structures were eulcidated as quercetin (1), rutin (2), vitexin (3), orientin (4), hyperin (5), tricin-7-O-b-D-glucopyranoside (6), chrysoeriol (7), tectochrysin (8) and luteolin-7-O-b-D-glucopyranoside (9), by means of spectroscopic methods, especially by 1H and 13C NMR, FAB-MS and GC, as well as by chemical methods and comparison with literature data.